Idealism and Materialism in Perception. (April 2015) - Rose, David; Brown, Dora
Koenderink (2014, Perception, 43, 1–6) has said most Perception readers are deluded, because they believe an 'All Seeing Eye' observes an objective reality. We trace the source of Koenderink's assertion to his metaphysical idealism, and point to two major weaknesses in his position—namely, its dualism and foundationalism. We counter with arguments from modern philosophy of science for the existence of an objective material reality, contrast Koenderink's enactivism to his idealism, and point to ways in which phenomenology and cognitive science are complementary and not mutually exclusive.